Between Fear and Disillusion in Argentina: Ahead of October's presidential elections, Kirchnerism pitches center, while current president Mauricio Macri embraces Peronists. The outcome—both political and economic—is impossible to predict. - Stefanoni, Pablo (NACLA Report on the Americas, 2019)
Between Fear and Disillusion in Argentina: Ahead of October's presidential elections, Kirchnerism pitches center, while current president Mauricio Macri embraces Peronists. Kirchnerism combined a nostalgia for the 1970s Peronist Youth radicalism - with its armed struggle for "national liberation" later becoming the target of the state-led terrorism of the military dictatorship - and a basically moderate reformist project. If Macri wins again, it will not only be the first time that a non-Peronist government completes a democratic term, it will also mean that his new center-right force will have put down roots in the national political terrain.